Tumor-Induced Osteomalacia Caused by a Parotid Basal Cell Adenoma Detected by 68Ga-DOTANOC PET/CT. (June 2018) - He, Qiao; Xu, Zeqing; Zhang, Bing; Hu, Wanming; Zhang, Xiangsong
Abstract : Abstract: Tumor-induced osteomalacia is a rare paraneoplastic syndrome, usually caused by small benign mesenchymal tumors. The tumors most arise within the extremities, whereas occurrence within the parotid gland is quite rare. A 54-year-old woman who presented with bone pain and muscle weakness for 2 years was clinically suspected of having tumor-induced osteomalacia. A 68 Ga-DOTANOC PET/CT was performed for localization of the causative tumor. The images demonstrated intense radiotracer accumulation in a soft tissue nodule in deep lobe of the right parotid gland. Subsequent surgical resection and pathologic analysis confirmed the diagnosis of parotid basal cell adenoma.